Prognostic role of indoleamine 2,3-dioxygenase 1 expression in solid tumors: A systematic review and meta-analysis - Zhang, Haiyan; Li, Jing; Zhou, Qi (Frontiers in Oncology, 2022)
Background: As a emerging immune checkpoint molecular, indoleamine 2,3-dioxygenase 1 (IDO1) is an immunosuppressive rate-limiting enzyme in metabolism of tryptophan to kynurenine. The expression of IDO1 affected the prognosis of patients in solid tumors. However, the results were controversial. To further investigate the role of IDO1 expression in solid tumors, we conducted the systematic review and meta-analysis. Methods: We searched the Web of Science, PubMed, Embase, Cochrane library databases, and CNKI to identify studies evaluating the prognostic value of IDO1 in solid tumors. Overall survival (OS), progression-free survival (PFS), and disease-free survival (DFS) were extracted as the outcome. Pooled hazard ratios (HRs) with 95% confidence intervals (CIs) were calculated by using fixed-effect/random-effect model, while heterogeneity, publication bias and sensitivity analysis between studies were also analyzed. Results: 18 studies with 2168 patients were included in this systematic review and meta-analysis. The results indicated that the high expression of IDO1 was associated with a shorter OS (n = 1926, HR = 1.60, 95% CI: 1.22-2.11, P = 0.001) and DFS (n = 327, HR = 2.65, 95% CI: 1.52-4.63, P = 0.001), while incorrelated with PFS (n = 428, HR = 1.76, 95% CI: 0.99-3.14, P = 0.240). There was significant heterogeneity between studies on OS (I2 = 77.8%, P < 0.001). Subgroup analysis showed age, gender, tumor type, follow-up period, and study quality were possible reasons for high heterogeneity. The result of trim-and-fill method indicated that publication bias for OS had no impact on our results. Egger’s test suggested no publication bias for PFS (P = 0.553) and DFS (P = 0.273). Furthermore, sensitivity analysis indicated the result was stable. Conclusion: High expression of IDO1 was associated with poor clinical outcomes, indicating that it could be a potential prognostic marker in various cancer types.